Governance for Inclusive Growth - Ivanyna, Maksym; Salerno, Andrea (Washington, D.C. : International Monetary Fund, 2021)
The government's ability to deliver inclusive growth crucially depends on the quality of governance. This paper reviews the linkages between governance and inclusive growth, and key policies to improve governance. The policies include (1) structural reform, automation, improving rules and procedures (including for fiscal and monetary policies) to limit the discretion and hence the space for policy errors; (2) human resource policies, capacity building, effective anti-corruption frameworks to incentivize public officials to make decisions in the best public interest; and (3) transparency, accountability, and inclusive political institutions to inform and monitor policymaking.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Administrative Processes in Public Organizations; Bureaucracy; Foreign Exchange; Informal Economy; Underground Econom